Characterization of the Body Mass Index and Height for Age in adolescents in a central Andean area of Ecuador - Jara-Porras, Jonathan (2018)
Introduction: The evaluation of the nutritional status and growth patterns in adolescents help to glimpse the eating habits and the quality of life that they lead. The standard of weight and height in Ecuador for this age group has not been well established yet, so it is useful to show the information collected in recent studies such as the present one. Objective: To determine, through nutritional indicators and anthropometric measures, the nutritional status of adolescents in a central Andean region of Ecuador. Methods: A mixed study of intentional and cross-sectional type was carried out in December 2017 in a sample of 238 men and 194 women from 13 to 17 years old, belonging to four Educational Centers in a central Andean area of Ecuador. The sample was stratified according to the age and sex. The indicators used were: body mass index (BMI) and height for age. The data were converted to z-scores and analyzed. Results: In BMI for age, the prevalence of risk of overweight reaches up to 30% in both groups women and men. In the categories obesity, emaciated and severely emaciated, the results reached a maximum of 10% in each group. In height for age, there is a minimum percentage of adolescents who have low height, which does not exceed 13% in the two groups. In severe short stature, only 3% were found in the group of 17-year-old women. In addition, it should be noted that in both groups there was generally a tendency toward the normal category in the nutritional indicators. Conclusions: Despite the fact that the vast majority of the observed groups is in a normal nutritional state, the present study documented the national reality of the double burden of malnutrition: the coexistence of emaciation cases together with risk of overweight, overweight and obesity cases. It is necessary to take actions that involve healthy eating habits from an early age to ensure optimal physical development and adequate school performance. © 2018 Sociedad espanola de dietetica. All rights reserved.